2011
DOI: 10.1097/rct.0b013e3181f31917
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Reversible Encephalopathy Syndrome (PRES) With Immune System Activation, VEGF Up-Regulation, and Cerebral Amyloid Angiopathy

Abstract: The case of a 75-year-old man with a history of lymphoma, recent upper respiratory tract infection, and a protracted course of encephalopathy is presented. Radiologically, findings were consistent with posterior reversible encephalopathy syndrome. A brain biopsy revealed evidence of endothelial activation, T-cell trafficking, and vascular endothelial growth factor expression, suggesting that systemic immune system activation may be involved with triggering posterior reversible encephalopathy syndrome. In addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Additional evidence from a brain biopsy included endothelial cell activation, T-cell trafficking, and increased expression of vascular endothelial growth factor, all indicating inflammation. 6 The authors concluded that PRES was triggered by inflammation from an upper respiratory infection the patient had earlier. In contrast, Bernstein and colleagues interpreted a similar finding as CAA-induced inflammation (CAA-I) and stated that the resolution of symptoms was due to successful steroid treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional evidence from a brain biopsy included endothelial cell activation, T-cell trafficking, and increased expression of vascular endothelial growth factor, all indicating inflammation. 6 The authors concluded that PRES was triggered by inflammation from an upper respiratory infection the patient had earlier. In contrast, Bernstein and colleagues interpreted a similar finding as CAA-induced inflammation (CAA-I) and stated that the resolution of symptoms was due to successful steroid treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, MRI with gradient-echo sequences now allows detection of small cortical and subcortical hemorrhages and thus, diagnosis of different CAA phenotypes including hemosiderosis (SH), acute cerebral ischemia, and superficial and posterior reversible encephalopathic syndrome (PRES). For the diagnosis of the latter, diffusion-weighted imaging and fluid-attenuated inversion recovery imaging (FLAIR) 69 are required.…”
mentioning
confidence: 99%
“…[9, 10] Endothelial dysfunction leading to vasoconstriction is thought to occur as a result of an underlying milieu of immune activation with elicitation of vasoactive factors that have a deleterious effect on the cerebral endothelium. [6, 11] Some form of immuno-modulation is common to most, if not all, PRES-predisposing conditions. [6] Additionally, in the rare reported biopsy/autopsy cases of PRES, immune activation as manifested by endothelial activation, T-cell trafficking, and vascular endothelial growth factor expression (VEGF) has been observed.…”
Section: Discussionmentioning
confidence: 99%
“…[6] Additionally, in the rare reported biopsy/autopsy cases of PRES, immune activation as manifested by endothelial activation, T-cell trafficking, and vascular endothelial growth factor expression (VEGF) has been observed. [11, 12] Thus, PRES is increasingly viewed as a state of hypoperfusion that occurs as a result of immune activation/dysfunction eventually leading to vasoconstriction within the cerebral arterial vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…However, watershed hypoperfusion and reduced brain perfusion in the posterior brain region have also been proposed by previous studies (13,14). At present, the intrinsic mechanism of RPES is considered to be an evolving systemic process with hypoperfusion/vasoconstriction and the development of brain toxicity, involving immune system activation, endothelial cell injury and inflammatory cytokine responses (15,16). The aforementioned toxicity-associated hypoperfusion/vasoconstriction leads to capillary bed injury and vasogenic edema.…”
Section: A B C Dmentioning
confidence: 99%